Praktik Jual Beli Ikan Melalui Tradisi Lelang Lebak Lebung Dalam Perspektif Ekonomi Islam (Studi Pada Masyarakat Desa Muara Batun Kecamatan Jejawi OKI) - Dedek Fania; Said Abdullah Syahab; M. Iqbal (CV. Cendikiawan Muda Sriwijaya, 2024)
This research is entitled Analysis of Fish Buying and Selling Practices through the Lebak Lebung Auction Tradition in the Study of Islamic Economics in Muara Batun Village, Jejawi Oki District. This research aims to find out how the process of buying and selling fish through the Lebang Lebung auction tradition is when viewed from an Islamic economic perspective. This research uses qualitative methods, with data sources in the form of primary data and secondary data with data collection techniques in the form of observation, interviews and documentation. The conclusion from this research is that in the practice of buying and selling fish using the Lebak Lebung auction system, if viewed from an Islamic economic perspective, there is still one condition that has not been fulfilled, namely that it is the object of the goods, so that this transaction cannot be said to be valid. It is as if the quality and quantity of fish in Lebak Lebung is not yet clear which is the object of buying and selling. Thus, failure to fulfill one of these conditions will result in this buying and selling containing elements of Ghror (unclarity) and maisir (gain or gambling) which are prohibited in Islam